THE EFFECT OF SELF-EFFICACY AND PROFESSIONAL ETHICS ON THE INTERNAL AUDIT QUALITY IN COMPANIES LISTED ON THE IRAN STOCK EXCHANGE - Murtadha Saleh Mahdi (Scholars Digest Publishing, 2023)
Auditor's self-efficacy is a feature arising from social cognition theories, leading to strengthening the internal audit quality as an effective factor of auditing's professional functions. This issue increases professional ethics in auditors. The present study investigates the effect of self-efficacy and professional ethics on the internal audit quality in companies listed on the Iran Stock Exchange. In this study, 312 internal auditors working in companies listed on the Tehran Stock Exchange participated. The study was conducted in 2023. The study tool was a questionnaire. To analyze and test the research hypotheses, the partial least squares analysis method was used. The results of the study hypotheses test revealed that the self-efficacy of the auditor improves the level of internal audit quality. Also, results revealed that professional ethics affects the positive relationship between self-efficacy and internal audit quality and positively strengthens this relationship.
Keywords: Self-efficacy, Professional ethics, Internal audit quality.